"Sheep are your mother" - Mlekuž, Dimitrij (Documenta Praehistorica, 2007)
This paper explores the relations between humans and animals through material culture, or more specifically, four-footed vessels also called rhyta (sing. rhyton). I want to suggest that rhyta are not merely artistic representations of something or some kind of cult paraphernalia, but that they embody effective social agency. I place them in the context of human-animal or interspecies politics in the Neolithic of the eastern Adriatic.
Keywords: vzhodni Jadran; arheološke najdbe; neolitik; materialna kultura; prazgodovinska umetnost; oblikovanje; motivi; živali; simboli; symbol